Innovative Approach in Preparing Young Educators for the Educational Process - Akbar Farkhodovich Norkulov (Peerian Journals Publishing, 2022)
This article talks about an innovative approach to training young pedagogues for the educational process. Based on the pedagogical data, the author studied and analyzed the specific aspects of the innovative approach to the training of young pedagogues on the basis of existininnovative approachg scientific literature
Keywords: pedagogues; educational process; innovative approach; development